2015
DOI: 10.1007/s00392-015-0831-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact on outcome of electrocardiographic early repolarization patterns among stroke patients: a prospective observational study

Abstract: ER is frequently found among patients with acute cerebrovascular events and is more prevalent in patients with hemorrhagic compared to ischemic events. Our study yields no evidence that ER is associated with worse outcome or mortality after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…As in earlier studies, this cohort also confirmed an extension of the QT period as a predictor of mortality in the 3-month course [27]. However, the early repolarization pattern, which has received much attention over the last 10 years, may be of secondary importance for stroke patients [28].…”
Section: Tachycardic Arrhythmiassupporting
confidence: 87%
“…As in earlier studies, this cohort also confirmed an extension of the QT period as a predictor of mortality in the 3-month course [27]. However, the early repolarization pattern, which has received much attention over the last 10 years, may be of secondary importance for stroke patients [28].…”
Section: Tachycardic Arrhythmiassupporting
confidence: 87%
“…The obvious advantages of this system are described as a minimization of lead complications as well as systemic infections. The system is especially attractive for patients with congenital heart disease [1], other rare entities impeding transvenous lead implantation [2,3] or electrical heart disease [4,5]. The early results of the worldwide EFFORTLESS-registry demonstrated an appropriate system performance.…”
Section: Sirsmentioning
confidence: 97%
“…The obvious advantages of this system are marketed as a minimization of lead complications and systemic infections. This innovative system can particularly be considered in patients with congenital heart disease, other rare entities impeding transvenous lead implantation, or electrical heart disease . The early results of the worldwide Evaluation oF FactORs ImpacTing CLinical Outcome and Cost EffectiveneSS (EFFORTLESS) registry suggested an appropriate system performance.…”
Section: Introductionmentioning
confidence: 99%
“…This innovative system can particularly be considered in patients with congenital heart disease, 3 other rare entities impeding transvenous lead implantation, 4 or electrical heart disease. 5,6 The early results of the worldwide Evaluation oF FactORs ImpacTing CLinical Outcome and Cost Effective-neSS (EFFORTLESS) registry suggested an appropriate system performance. Occurrence of arrhythmic events and inappropriate shocks resembled those reported for conventional transvenous ICD systems.…”
mentioning
confidence: 99%